A european shipping companies survey on arctic shipping : expectation vs. reality - Fournier, Mélanie; Lasserre, Frédéric; Têtu, Pierre-Louis; Beveridge, Leah (Conseil québécois d'études géopolitiques, 2020)
Operating a vessel in Arctic waters is complicated, costly and risky. Arctic shipping has gained growing attention since the early 2000s as a result of global warming. Although the duration, extent and nature of ice coverage are changing, the annual variability and a significant degree of uncertainty will remain. However, although the feasibility of increasing maritime traffic in the Arctic is tightly related to ice conditions, it is also coupled to governance, geopolitical factors, infrastructure development, prices of resources, and the interest of shipping companies. This paper describes the results of a study conducted from 2015 until 2016 on European shipping companies and their perceptions of Arctic shipping. The purpose of this survey was to take into account the operational point of view of shipping companies, and determine the interest for the Arctic market and whether the current trend was reflected the boom in the industry anticipated in the media. L’exploitation d'un navire dans les eaux arctiques est compliquée, coûteuse et risquée. La navigation dans l'Arctique a attiré de plus en plus l'attention depuis le début des années 2000 en raison du changement climatique. Bien que la durée, l'étendue et la nature de la couverture de glace changent, la variabilité annuelle et un degré important d'incertitude demeureront. Cependant, bien que la faisabilité d'augmenter le trafic maritime dans l'Arctique soit étroitement liée aux conditions des glaces, elle est également associée à la gouvernance, aux facteurs géopolitiques, au développement des infrastructures, aux prix des ressources et à l'intérêt des compagnies de navigation. Cet article décrit les résultats d'une étude menée de 2015 à 2016 sur les compagnies maritimes européennes et leur perception du transport maritime dans l'Arctique. Le but de cette enquête était de prendre en compte le point de vue opérationnel des compagnies de navigation, et d’évaluer leur intérêt pour le marché de l'Arctique.